Identifikasi Penyebab Korupsi dalam Prosedur Pengadaan Barang dan Jasa Pemerintah - Ainiel Riany Putri; Cahya Dhea Ningrum; Diana Raihannisa; Icce Leni Damanik; Novitayana Br Sinurat; Sabrina Salsabilah; Oktarini Khamilah Siregar (Masyarakat Ekonomi Syariah Bogor, 2024)
This study shows solution to prevent a corruption in government procurement. This study was conducted using descriptive qualitative methods with secondary data collection through a literature review. The results of the research show that cases of corruption in the procurement of government goods and services in Indonesia are due to the lack of strong regulations for procurement of government goods/services and the ineffectiveness of the government procurement system for goods/services, such as poor quality and quantity of goods, wrong goods obtained, lack of clarity in other technical requirements. , as well as the slow implementation of procurement and delivery of required goods and services, which makes beneficiaries disappointed. Maladministration is also seen as an important component of corruption in goods and services procurement procedures.